Determinants of the economic viability of mallee eucalypts as a short rotation coppice crop integrated into farming systems of Western Australia - Spencer, Beren; Abadi, Amir; Bartle, John; Sudmeyer, Robert; van Gent, Sarah; Gibberd, Mark; Zerihun, Ayalsew (Wiley-Blackwell, 2020)
© 2020 The Authors. GCB Bioenergy Published by John Wiley & Sons Ltd